Analisis Kerusakan Trim Air Pressure Regulating and Shutoff Valve Pada Pesawat Boeing 737-800 Menggunakan Metode Failure Mode and Effect Analysis (FMEA) - Rizwan Maulana; Freddy Franciscus; Mufti Arifin (FTK UNSURYA, 2022)
Air Conditioning (AC) is the one of system in aircraft to make a passanger and all cabin crew comfortable. Trim Air Pressure Regulating and Shutoff Valve or also known as Trim Air PRSOV is a component on the Boeing 737-800 aircraft to regulate flow of hot air constantly before entering the aircraft cabin. Refering to the data for the last 6 years, the replacement of the component belonging to one of the Indonesian national flight carrier using Boeing 737-800 aircraft was the occurance of 84 times the cooling system failure which caused the light indiacator in the cockpit to light up. Among them happened 70 times unscheduled maintenance and 14 times scheduled maintenance. Thus, this essay was made to analyze the causes of the damage that occurred to the Trim Air PRSOV. The method used in this research is Failure Mode and Effect Analysis (FMEA) is the technique used to find, identify and eliminate failures or damage to a system or process. The first step is to analyze using a Pareto diagram and then continue with the FMEA method so that an analysis of the damage that often occurs is damage to the diaphragm with 42% damage with an RPN value of 389.1, erosion on the ring seal with 22% damage with an RPN value of 376 and shaft seal damaged with 12% damage with an RPN value of 295.1 for it requires aggressive treatment. Therefore, repairs with a long TAT of 14 days are expected to increase the reliability of the PRSOV Trim Pressure component. For this reason, repairs are carried out with a long TAT of 14 days, it is hoped that there will be an increase in the reliability of the PRSOV Trim Pressure componen.